Efficiency comparison of four high-fidelity DNA polymerases for dengue virus detection and genotype identification in field-caught mosquitoes - Sittivicharpinyo, Thikhumporn; Wonnapinij, Passorn; Surat, Wunrada (Agriculture and Natural Resources, 2018)
Dengue disease is an important arboviral disease caused by the bite of a dengue virus (DENV)-infected mosquito vector, especially Aedes aegypti. This disease is widely spread throughout both the tropical and temperate zones. DENV causes deaths every year, especially in children, thus emphasizing the need to improve DENV surveillance. Early detection and accurate serotype and genotype identification is one approach for improving DENV surveillance; therefore, this study evaluated the efficiency of four highfidelity DNA polymerasesd-AccuPrime™ Taq, Platinum® Pfx, Q5® High-Fidelity, and KOD FX Neo-in amplifying the C/prM junction and the NS5 and E genes that have been widely used to detect DENV and identify a DENV serotype and genotype using a method based on reverse transcription polymerase chain reaction. By amplifying the C/prM junction from DENV isolated from the viral culture, Q5 was selected for screening DENV infection in field-caught mosquitoes. The results of screening 2791 female mosquitoes collected from 2011 to 2015 showed that all DENV serotypes circulated in Thailand with the highest frequency serotype being DENV-3. Then, cDNAs of four pooled mosquitoes detected to carry four different serotypes were selected to examine the efficiency of the DNA polymerases. The results showed that Pfx had the highest efficiency for amplifying the C/prM junction and the partial NS5 gene, while AccuPrime was the most efficient enzyme for amplifying the complete E gene. Hence, these results suggested that both the type of sample and the region of the DENV genome should be considered when choosing an efficient DNA polymerase.